Report on a pilot study to crowdsource farmgate prices for legumes in southern Malawi - Ochieng, Dennis O. (International Food Policy Research Institute, 2019)
Little is known about farmgate prices in Malawi since data on the price trends are inconsistently collected. Yet this is important information for assessing the performance of agricultural markets. This report summarizes the findings from a pilot study to crowdsource farm gate prices for pigeon peas and chickpeas through the Farm Radio Trust (FRT) platform. In a series of radio ‘jingles’ and short message service (SMS) ‘pushes’, farmers were invited to report the prices and locations at which they had sold their pigeon peas and chickpeas to a toll-free number or using SMS. The phone numbers of farmers who responded were entered into a weekly draw with the possibility of winning a MWK25,000 coupon redeemable at a major agricultural input dealer. Between August 15, 2019 and November 1, 2019, 637 farmers called or sent short message service (SMS) texts to a toll-free number to report their sales, volume sold, and the type of buyer and location for sales of pigeon peas or chickpeas during the 2019 marketing season. At the end of the pilot, a follow up telephone survey of 468 of the 637 farmers was conducted to obtain detailed information on farmers’ production and marketing activities that were not captured in the initial phone calls.